NF-κB dysregulation in multiple myeloma. (August 2016) - Matthews, Geoffrey M.; de Matos Simoes, Ricardo; Dhimolea, Eugen; Sheffer, Michal; Gandolfi, Sara; Dashevsky, Olga; Sorrell, Jeffrey D.; Mitsiades, Constantine S.
Abstract: The nuclear factor-κB (NF-κB) transcription factor family plays critical roles in the pathophysiology of hematologic neoplasias, including multiple myeloma. The current review examines the roles that this transcription factor system plays in multiple myeloma cells and the nonmalignant accessory cells of the local microenvironment; as well as the evidence indicating that a large proportion of myeloma patients harbor genomic lesions which perturb diverse genes regulating the activity of NF-κB. This article also discusses the therapeutic targeting of the NF-κB pathway using proteasome inhibitors, a pharmacological class that has become a cornerstone in the therapeutic management of myeloma; and reviews some of the future challenges and opportunities for NF-κB-related research in myeloma.